Flexible logistic processes with the use of modular loading units - Wiśnicki, Bogusz; Dzhuguryan, Tygran (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2018)
The aim of the article is to present an innovative concept of modular load units which increase the efficiency of production processes as well as transport and logistics. The characteristic of the original concept of modular load units are presented, with their technical and technological description and assembly. The article ends with a synthetic analysis of the effectiveness of the proposed solutions. The applications contain a description of the possibilities of further implementation and development of the technology under study. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)